Verbalizing bifurcation situations : proper names referring to events in media discourse - Rodríguez Pedreira, Nuria; Konowska, Agnieszka (The Art of Living, Surviving, Reviving. Studies in Linguistics. The 50th Anniversary of Romance Studies at the University of Łódź, 2022)
The COVID-19 pandemic has created a situation of bifurcation within societies: we are talking about a world before and after the coronavirus. The name of the city of Wuhan, its “cradle”, has become a fatal symbol. This contribution examines the discursive functioning of proper names referring to events of this type (Wuhan, Chernobyl, 9/11) and how they meet certain needs of speakers at times of “rupture”. We speak about them as about proper denominations (Bosredon and Tamba 1995), words-events (Moirand 2007) or proper names referring to events (Krieg-Planque 2009) because they cover both some typical features of common names and proper names. We first ask about the activity of nomination through the designations used, often concurrent, and on their functioning in their relation to the co(n)text, but also to previous discourses (Moirand and Reboul-Touré 2015). To name something from an enunciative point of view is to select a designation among others available, and this with an essentially intentional aim. This is what we focus on in a second step, by identifying the role of the proper names of events in argumentative euphemization and dysphemization, through the analysis of a few examples from our corpus.